Multicentre phase II trial of near‐infrared imaging in elective colorectal surgery. Issue 10 (16th April 2018) - Ris, F.; Liot, E.; Buchs, N. C.; Kraus, R.; Ismael, G.; Belfontali, V.; Douissard, J.; Cunningham, C.; Lindsey, I.; Guy, R.; Jones, O.; George, B.; et al.
Abstract : Background: Decreasing anastomotic leak rates remain a major goal in colorectal surgery. Assessing intraoperative perfusion by indocyanine green (ICG) with near‐infrared (NIR) visualization may assist in selection of intestinal transection level and subsequent anastomotic vascular sufficiency. This study examined the use of NIR‐ICG imaging in colorectal surgery. Methods: This was a prospective phase II study (NCT02459405) of non‐selected patients undergoing any elective colorectal operation with anastomosis over a 3‐year interval in three tertiary hospitals. A standard protocol was followed to assess NIR‐ICG perfusion before and after anastomosis construction in comparison with standard operator visual assessment alone. Results: Five hundred and four patients (median age 64 years, 279 men) having surgery for neoplastic (330) and benign (174) pathology were studied. Some 425 operations (85·3 per cent) were started laparoscopically, with a conversion rate of 5·9 per cent. In all, 220 patients (43·7 per cent) underwent high anterior resection or reversal of Hartmann's operation, and 90 (17·9 per cent) low anterior resection. ICG angiography was achieved in every patient, with a median interval of 29 s to visualization of the signal after injection. NIR‐ICG assessment resulted in a change in the site of bowel division in 29 patients (5·8 per cent) with no subsequent leaks in these patients. Leak rates were 2·4 per cent overall (12 of 504), 2·6 per cent for colorectal anastomoses and 3 per cent for low anterior resection. When NIR‐ICG imaging was used, the anastomotic leak rates were lower than those in the participating centres from over 1000 similar operations performed with identical technique but without NIR‐ICG technology. Conclusion: Routine NIR‐ICG assessment in patients undergoing elective colorectal surgery is feasible. NIR‐ICG use may change intraoperative decisions, which may lead to a reduction in anastomotic leak rates. Abstract : Appears to reduce leaks